Energy Transition Policy Analysis in Indonesia (Forum Ilmu Sosial, 2022)
This article aims to identify several aspects of the problem in Indonesian energy supply, describe the energy transition policy as a solution to overcome the problems, and study the energy transition in several other countries, especially in Asia, to be used as an example in formulating the right energy transition policy for this country. This problem is focused on the pattern of energy supply in Indonesia and why the energy transition policy has not been optimal. This study used the theoretical reference from Donald S. Van Meter and Carl E. Van Horn: policy target standards, resources, communication between organizations and strengthening activities, characteristics of implementing agents, and social, economic, and political conditions. The data used are studies in the form of reports, papers, or articles in a mass media news column. To encourage the energy transition policy, it is necessary to have a Renewable Energy Subsidy. The analysis was conducted qualitatively. This study's results show that the People's Representative Council of the Republic of Indonesia needs to finalize the regulations that are being drafted, namely the New and Renewable Energy Bill, which is then translated into the vision of the Ministry of Energy and Mineral Resources into an integrated policy framework to overcome obstacles to the development of Renewable Energy. Renewable energy subsidies are needed to encourage energy transition policy to reduce the electricity bills generated from Renewable Energy technology.